Differential expression on mitochondrial tryparedoxin peroxidase (mTcTXNPx) in Trypanosoma cruzi after ferrocenyl diamine hydrochlorides treatments - Kohatsu, Andrea A. N. [UNESP]; Silva, Flavia A. J. [UNESP]; Francisco, Acacio I.; Rimoldi, Aline [UNESP]; Silva, Marco T. A.; Vargas, Maria D.; Rosa, Joao A. da [UNESP]; Cicarelli, Regina M. B. [UNESP] (Elsevier B.V., 2017)
Resistance to benznidazole in certain strains of Trypanosoma cruzi may be caused by the increased production of enzymes that act on the oxidative metabolism, such as mitochondrial tryparedoxin peroxidase which catalyses the reduction of peroxides. This work presents cytotoxicity assays performed with ferrocenyl diamine hydrochlorides in six different strains of T. cruzi epimastigote forms (Y, Bolivia, SI1, SI8, QMII, and SIGR3). The last four strains have been recently isolated from triatominae and mammalian host (domestic cat). The expression of mitochondrial tryparedoxin peroxidase was analyzed by the Western blotting technique using polyclonal antibody anti mitochondrial tryparedoxin peroxidase obtained from a rabbit immunized with the mitochondrial tryparedoxin peroxidase recombinant protein. All the tested ferrocenyl diamine hydrochlorides were more cytotoxic than benznidazole. The expression of the 25.5 kDa polypeptide of mitochondrial tryparedoxin peroxidase did not increase in strains that were more resistant to the ferrocenyl compounds (SI8 and SIGR3). In addition, a 58 kDa polypeptide was also recognized in all strains. Ferrocenyl diamine hydrochlorides showed trypanocidal activity and the expression of 25.5 kDa mitochondrial tryparedoxin peroxidase is not necessarily increased in some T. cruzi strains. Most likely, other mechanisms, in addition to the over expression of this antioxidative enzyme, should be involved in the escape of parasites from cytotoxic oxidant agents. (C) 2016 Sociedade Brasileira de Infectologia. Published by Elsevier Editora Ltda. This is an open access article under the CC BY-NC-ND license.
Keywords: Trypanosoma cruzi; Ferrocenyl diamine hydrochlorides; Mitochondrial tryparedoxin; peroxidase (mTcTXNPx); Oxidative stress mechanisms